Efficient catalytic degradation of methylene blue by a novel Fe3+-TiO2@CGS three-dimensional photoelectric system - Li, Jian; Wang, Yufei; Guo, Fanhui; Chen, Juan; Wang, Jinxi; Fan, Xiaoyong; Li, Baoning; Verma, Santosh Kumar; Wei, Qingbo; Yan, Long; Wu, Jianjun (Frontiers in Chemistry, 2022)
In this study, a novel three-dimensional photoelectric system was designed and constructed for the degradation of methylene blue (MB) via photocatalysis, electrocatalysis, and photoelectric catalysis. To this end, a Ti/RuO2-IrO2-SnO2-CeO2 electrode was prepared via a thermal oxidation coating method and used as a dimensionally-stable anode (DSA). The cathode was made of a titanium sheet with Fe3+-doped TiO2 loaded on coal gasification slag (CGS) (Fe3+-TiO2@CGS) as a photocatalyst. The factors affecting the degradation efficiency, such as the supporting electrolyte, current density, and initial pH were systematically investigated. The results revealed Fe3+-TiO2@CGS three-dimensional photoelectric system exhibiting efficient synergistic performance of photocatalysis and electrocatalysis with a synergistic factor of 1.11. Photo-generated holes (h+) were generated by light irradiation and direct anodic oxidation. Furthermore, hydroxyl radicals (HO·) radicals were induced via other pathways. Such active species showed highly-oxidizing abilities, beneficial to the degradation of methylene blue (MB). The representative Fe3+-TiO2@CGS three-dimensional photoelectric system showed super high degradation efficiency at pH 11 and current density of 18.76 mA cm−2. Using NaCl as a supporting electrolyte, the degradation yield reached 99.98% after 60 min of photoelectrical treatment. Overall, the novel Fe3+-TiO2@CGS three-dimensional photoelectrical system looks very promising for the highly efficient catalytic degradation of organic contaminants.